Efeito do uso da terra sobre a diversidade funcional de peixes em riachos da Mata Atlântica. - Batista, Marcella Maria Ida (2023)
The investigation of anthropogenic impacts on freshwater ecosystems has become a growing concern among researchers. Recent studies have employed the functional diversity approach, utilizing species traits for a better understanding of the organisms roles in ecosystem functioning. Based on samplings conducted in 16 streams in the North and Northwest regions of the state of Paraná, Brazil, the objective was to identify and characterize fish assemblages in streams within the Atlantic Forest Biome, correlating them with environmental variables and different land uses. Evaluated environmental parameters included water velocity, turbidity, temperature, and dissolved oxygen. Three functional indices were used for characterization: Functional Richness (FRic), Functional Evenness (FEve), and Functional Dispersion (FDis). Different stream land uses were considered, classified as urban, rural, and within Conservation Units. Abiotic characteristics played a significant role in selecting fish functional traits, demonstrating the influence of the environment on functional diversity. Analyzing the relationships between functional diversity indices and environmental variables allowed understanding complex interactions among these parameters in different land uses. This study emphasizes the importance of integrated ecosystem approaches to promote stream management and conservation practices. Riparian vegetation presence, pollution control, and water quality improvement are essential measures to ensure the healthy functioning of freshwater ecosystems. Additionally, Protected areas play a crucial role in biodiversity protection and the provision of ecosystem services.